Y2K : how the 2000s became everything : essays on the future that never was - Shade, Colette (DeySt., an imprint of William Morrow, 2025)
"Y2K is a delightfully nostalgic and bitingly told exploration about how the early 2000s forever changed us and the world we live in."--